The PENGARUH MYOFASCIAL TRIGGER POINT RELEASE DAN MYOFASCIAL RELEASE TERHADAP PENURUNAN NYERI PADA TENSION HEADACHE: NARRATIVE REVIEW: PENGARUH MYOFASCIAL TRIGGER POINT RELEASE DAN MYOFASCIAL RELEASE TERHADAP PENURUNAN NYERI PADA TENSION HEADACHE: NARRATIVE REVIEW - Mutiara Husnayati; Lailatuz Zaidah; Asyhara Naela Arifin (Jurnal Kesehatan Al-Irsyad, 2021)
Tension headache is a type of pain referred to the surface of the head that comes from the inner structure. Tension headaches that are aggravated by coughing, exertion, sexual activity, Valsalva maneuver, or sleep suggest arteriovenous malformation, subarachnoid hemorrhage, or vascular disease. The study aimed to determine the effect of myofascial release and myofascial trigger point release in reducing pain in tension headaches. The study applied narrative review using the PICO method. Journal searches were conducted on online journal portals such as Google Scholar, PubMed, and Science direct. Myofascial release and myofascial trigger point release can reduce pain in tension headaches from 10 journals that have been reviewed. Suggestion in this study for someone with tension headache condition, it is recommended to do myofascial release or myofascial trigger point release in reducing pain in tension headache.